Trends and outlook report on key agriculture and rural development indicators in Kenya - Ogada, Maurice; Guthiga, Paul; Massawe, Stella (International Food Policy Research Institute, 2011)
This annual trends report for agricultural and rural development indicators is a monitoring and evaluation tool. It can be used to facilitate critical assessment of the progress being made in implementing and achieving the goals of Comprehensive African Agriculture Development Program (CAADP) and other national developmental goals. CAADP aims at helping African countries to achieve high economic growth through agriculture-led development. The agricultural sector in Kenya contributes significantly to the national Gross Domestic Product (GDP) and employment. It provides a livelihood base for the majority of the population that live in the rural areas.